Pengaruh Personal Background dan Pengetahuan Dewan Tentang Anggaran Terhadap Kinerja DPRD Kota Padang Dalam Pengawasan Keuangan Daerah - Imelda Sari (Majalah Sainstekes, 2017)
This research aims to examine the influence of personal background, and council budget knowledge toward the performance of DPRD on region financial control. A controlling from the legislative board in the local economic policy execution is an important thing to realize the right regional financial management. The population of research is 45 members of DPRD Padang City. The entire community in this study serves as the sample with the census method. The data consist of primary data that taken from questionnaires distributed directly to respondents. The analyze method used in this study is multiple regression linear model, using F test, and t-test is simultaneously and partially applied. The result of this research and hypothesis testing shows that simultaneously personal background and council budget knowledge had the significant influence on the performance of DPRD on region financial control. Partially, indicators of personal background have no significant impact on the performance of DPRD on region financial control. Variables of council budget knowledge also have no influences toward the achievement of DPRD on region financial control. One of indicators council budget knowledge has positive and significant influence toward the performance of DPRD on region financial control is training about region financial control.